Classifications of Knowledge in Classical Islamic Mysticism: from Eastern Sufi Sources to the Writings of Muḥyī l-Dīn Ibn al-ʿArabī - Ebstein, Michael (Studia Islamica, 2020)
The following article aims at analyzing various classifications of knowledge that are found in the literature of classical Islamic mysticism. The discussion focuses on two main corpora: Sufi writings, composed in the central and eastern parts of the Islamic world, and works by the Andalusī mystics or theosophists Ibn Masarra (d. 319/931), Ibn Barraǧān (d. 536/1141), Ibn Qasī (d. 546/1151), and Muḥyī l-Dīn Ibn al-ʿArabī (d. 638/1240). The article examines the discrepancies between the Eastern-Sufi and Andalusī taxonomies of knowledge, in an attempt to highlight the typological differences between these two mystical traditions of classical Sunnī Islam.